PENGARUH KEPATUHAN WAJIB PAJAK, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN BADAN (STUDI KASUS DI KPP PRATAMA PATI TAHUN 2016-2019) - Sulistyorini, Eka; Latifah, Nurul (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of corporate income tax receipts. The independent variables include taxpayer compliance, tax audit, and tax collection. This study uses primary data derived from questionnaires. The population in this study were companies registered with KPP Pratama Pati for the period 2016–2019 that had NPWP. The sampling technique used is purposive sampling and the number of samples is 100 data. The data analysis method used multiple linear regression. The results of this study indicate that taxpayer compliance has a positive effect on corporate income tax receipts, tax audits have a positive effect on corporate income tax revenues, and tax collection has a positive effect on corporate income tax revenues. Taxpayer compliance, tax audit, and tax collection simultaneously have a positive effect on corporate income tax receipts.Keywords: Taxpayer Compliance, Tax Audit, Tax Collection, Corporate Income Tax Receipt.